The evaluation of land suitability toUpland rice (Oryza sativaL.)and Onion (Allium ascalonicum L.) in Kualuh Hulu SubdistrictOfNorth Labuhanbatu District - Khairi Rizki Siregar; zulkifli Nasution; Bintang Sitorus (Universitas Sumatera Utara, 2019)
The objective of this researchis to evaluate the land suitability Upland rice (Oryza sativa L.)and Onion (Allium ascalonicumL.) in Kualuh Hulu Subdistrict of North Labuhanbatu District. The methode of this research is the survay method. From the results of the overlay from the map of soil types, map of topography, and map of height place, retrieved 9 units of land use map. SPL 1 has a land area of22.273,98 hectares, SPL 2 has a land area of 12.248 hectares, SPL 3 has a land area of 8.571,24 hectares, SPL 4 has a land area of 8.015,46hectares, SPL 5 has a land area of 4.736,61 hectares, SPL 6 has a land area of 3.154,86 hectares, SPL 7 has a land area of 2.044,73 hectares, SPL 8 has a land area of 1.445,39 hectares and SPL 9 has a land area of 946,28hectare. The conclusionof this research showed the highest potential of land suitability classes in set of land 1 is upland rice ( S3 rc ) and onion ( S3 wa, rc ),in set of land 2 is upland rice (N rc) and onion( N rc ), in set of land 3 is upland rice ( S1 ) and onion ( S3wa ), in set of land4 is upland rice( N rc ) andonion ( N rc ), in set of land 5 is upland rice (S3 rc ) and onion ( S3 wa rc ), in set of land 6 is upland rice (S1) and onion (S3 wa ), in set of land 7 isupland rice(S3 rc ) and onio (S3 wa rc), in set of land 8 is upland rice (S3 rc ) and onion ( S3 wa rc ) and in set of land 9 is upland rice ( S3 rc ) and onion (S3 wa rc). Keywords : Land suitability, Onion, Upland rice